A mussel‐inspired strategy toward antimicrobial and bacterially anti‐adhesive soy protein surface. Issue 2 (14th October 2019) - Jin, Shicun; Song, Xiangshuo; Li, Kuang; Xia, Changlei; Li, Jianzhang
Abstract: Biopolymer products are widely used in our everyday life, however, the poor antimicrobial nature dramatically limits their applications. Therefore, it is essential to improve the antibiotic performance of these biopolymer products. In this study, soy protein isolate (SPI)‐based films with antimicrobial and antifouling function were fabricated through a dip‐coating method. Briefly, mussel‐inspired polydopamine was coated onto the surface of SPI film, followed by depositing silver nanoparticles (AgNPs) on the film for yielding an antimicrobial film, named S‐DA‐Ag. Subsequently, octadecyltrichlorosilane (OTS) molecular was attached on the S‐DA‐Ag film. Elemental and morphological surface analyses verified the successful coating for each step. The S‐DA film decorated only with AgNPs exhibited an effective antimicrobial activity against Escherichia coli and Staphylococcus aureus but failed to prevent bacterial attachment. However, the number of attached bacterial cells significantly decreased for the OTS‐coated S‐DA‐Ag film. Additionally, the resultant SPI‐based films displayed excellent mechanical performance and remarkably improved water resistance, dramatically benefiting their practical applications. This novel design can endow the antimicrobial and antifouling properties to the SPI‐based films and enhance their mechanical properties and water resistance, which might expand their potential applications in the healthcare and biomedical fields.